Fast spontaneous recovery from acute necrotizing eosinophilic myopericarditis without need for immunosuppressive therapy: a case report of a 27-year-old male. Issue 4 (17th June 2020) - Kindermann, Michael; Sood, Nitin; Ehrlich, Peter; Klingel, Karin
Abstract: Background: Eosinophilic myocarditis (EM) is rare but accounts for 12–22% of histologically proven acute myocarditis cases. Acute necrotizing EM is considered an aggressive, life-threatening disease which is usually treated by high-dose corticosteroid therapy. Case summary: We report the case of a 27-year-old man with acute severe pericarditic chest pain, moderately reduced left ventricular (LV) ejection fraction, and a small pericardial effusion. Troponin I level was highly elevated in the absence of coronary artery disease, leading to the diagnosis of acute myopericarditis. In the absence of blood eosinophilia and despite a negative cardiac magnetic resonance study, LV endomyocardial biopsy revealed an acute necrotizing EM. With conventional antiphlogistic and heart failure therapy, the patient became symptom-free and inflammatory and cardiac necrosis markers as well as LV ejection fraction normalized within days. Thus, in the absence of a systemic hypereosinophilic disorder, there was no need for steroid therapy. Long-term follow-up over 12 months showed sustained normalization of cardiac structure and function. Discussion: Acute necrotizing eosinophilic myopericarditis is not always a dreadful cardiac disease. There are idiopathic cases which may quickly resolve without immunosuppression. There seems to be a publication bias towards critical cases.